2012
DOI: 10.1038/cddis.2012.160
|View full text |Cite
|
Sign up to set email alerts
|

miR-204 targets Bcl-2 expression and enhances responsiveness of gastric cancer

Abstract: Micro RNAs (miRs) are small non-coding RNAs aberrantly expressed in human tumors. Here, we aim to identify miRs whose deregulated expression leads to the activation of oncogenic pathways in human gastric cancers (GCs). Thirty nine out of 123 tumoral and matched uninvolved peritumoral gastric specimens from three independent European subsets of patients were analyzed for the expression of 851 human miRs using Agilent Platform. The remaining 84 samples were used to validate miRs differentially expressed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
138
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 27 publications
15
138
1
1
Order By: Relevance
“…47,48 Recent studies showed that SIRT1 is a target for miR-204 and is functionally critical for multiple cancer phenotypes such as migration/invasion, EMT, and resistance to anoikis. 17,49,50 Consistent with these studies, we showed that both MALAT1 and SIRT1 bound to the same site on miR-204, and therefore, in addition to targeting miR-204 to Ago2-mediated silencing, MALAT1 may also compete with SIRT1 for binding to miR-204, both mechanisms releasing SIRT1 from the negative control by miR-204.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Recent studies showed that SIRT1 is a target for miR-204 and is functionally critical for multiple cancer phenotypes such as migration/invasion, EMT, and resistance to anoikis. 17,49,50 Consistent with these studies, we showed that both MALAT1 and SIRT1 bound to the same site on miR-204, and therefore, in addition to targeting miR-204 to Ago2-mediated silencing, MALAT1 may also compete with SIRT1 for binding to miR-204, both mechanisms releasing SIRT1 from the negative control by miR-204.…”
Section: Discussionmentioning
confidence: 99%
“…As Ezrin is critical to Ras activation and is predicted to be a target of miR-204, this indicates that miR-204 downregulation may be a novel mechanism for aberrant Ras activation in gastric tumorigenesis (Lam et al, 2011). Further, miR-204 may target Bcl-2 expression and increase the responsiveness of GC cells to 5-fluorouracil and oxaliplatin treatment, indicating that miR-204 might be a therapeutic target for improving the prognosis of GC (Sacconi et al, 2012). Wang et al (2014) compared differentially expressed miRNAs between Helicobacter pylori-related gastritis and gastric intestinal metaplasia lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, downregulation of miR-204 has been documented in several types of cancers. [37][38][39][40][41] Decreased expression of miR-204 results in overexpression of its target, myeloid cell leukemia sequence 1 (Mcl-1) mRNA, and induces anti-apoptotic signaling in pancreatic cancers. 42 miR-204 also regulates expression of an oncogene, neurotrophic receptor tyrosine kinase B, and promotes metastasis in endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%